False transfixation of the liver using an endoscopic gastrostomy tube: Do not always believe in radiologic images - Nunes, Gonçalo; Rodrigues Alves, Teresa; Luz, Carlos; Vieira, Isabel; Carmona, Luísa; Santos, Carla Adriana; Fonseca, Jorge (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Nunes G, Alves TR, Luz C, et al. False transfixation of the liver using a percutaneous endoscopy gastrostomy tube: Do not always believe in radiologic images. Turk J Gastroenterol 2017; 28: 526-7.